Perovskite Oxide Based Electrodes for High-Performance Photoelectrochemical Water Splitting - Wang, Wei; Xu, M.; Xu, Xiaomin; Zhou, W.; Shao, Zongping (WILEY-V C H VERLAG GMBH, 2020)
Photoelectrochemical (PEC) water splitting is an attractive strategy for the large-scale production of renewable hydrogen from water. Developing cost-effective, active and stable semiconducting photoelectrodes is extremely important for achieving PEC water splitting with high solar-to-hydrogen efficiency. Perovskite oxides as a large family of semiconducting metal oxides are extensively investigated as electrodes in PEC water splitting owing to their abundance, high (photo)electrochemical stability, compositional and structural flexibility allowing the achievement of high electrocatalytic activity, superior sunlight absorption capability and precise control and tuning of band gaps and band edges. In this review, the research progress in the design, development, and application of perovskite oxides in PEC water splitting is summarized, with a special emphasis placed on understanding the relationship between the composition/structure and (photo)electrochemical activity.